GSK3β 5'-flanking DNA Methylation and Expression in Alzheimer's Disease Patients - Nicolia, Vincenzina; Ciraci, Viviana; A. Cavallaro, Rosaria; Ferrer, Isidre; Scarpa, Sigfrido; Fuso, Andrea (Current Alzheimer Research, 2017)
Background: The GSK3β has been associated to pathological functions in neurodegenerative diseases. This kinase is involved in hyperphosphorylation of microtubule-associated tau protein, leading to aggregation andformation of NFTs. It has clearly been shown that GSK3β is regulated at posttranslational level: phosphorylation at Tyr216 activates kinase, while phosphorylation at Ser9 is essential to inhibit its activity. Objectives: At present, there are contradictory findings about the possibility that GSK3β may be regulated at gene level. Previous data showed overexpression of GSK3β mRNA in hypomethylating conditions, pointing out to the existence of epigenetic mechanisms responsible for GSK3β gene regulation. Analysis of human GSK3β promoter through bisulphite modification, both in neuroblastoma cells and in postmortem frontal cortex from AD patients (AD patients both at Braak stages I-II and at stages V-VI) , allowed us to characterize the methylation pattern of a putative CpG islands in human GSK3β 5'- flanking region. Results: The analysis evidenced overall hypomethylation of CpG and non-CpG cytosine residues both in cells and in human brain (AD patients and control subjects). We found that GSK3β mRNA was overexpressed only in patients with initial AD, with no effect on the levels of the protein. On the other hand, we unexpectedly observed the decrease of the inactive GSK3β in cortex from AD patients at Braak stages I-II, whereas considerable increase was observed in AD patients at stages V-VI compared to the control subjects. Conclusions: These results point out that GSK3β hyperactivity, and then NFTs formation, could come into function at an early stage of the disease and then turn off at the last stages.
Keywords: DNA methylation